THE CRITERION OF A NORMALLY PROVIDENT INSURED: AN INTERPRETATION - Cooper, Daniel (Assurances, 1997)
This document is divided into two parts. The first examines the history of the duty of disclosure, and its exceptions, in the context of the reform of the new Civil Code of Quebec, and the applicable laws of other provinces in Canada, as well as the laws of France, England, and the United States. The second interprets the Civil Code's new disclosure criterion: that of the normally provident insured, founded at article 2409 of the new Civil Code of Quebec.